2018
DOI: 10.1111/evo.13475
|View full text |Cite
|
Sign up to set email alerts
|

Rates of molecular evolution in tree ferns are associated with body size, environmental temperature, and biological productivity

Abstract: Variation in rates of molecular evolution (heterotachy) is a common phenomenon among plants. Although multiple theoretical models have been proposed, fundamental questions remain regarding the combined effects of ecological and morphological traits on rate heterogeneity. Here, we used tree ferns to explore the correlation between rates of molecular evolution in chloroplast DNA sequences and several morphological and environmental factors within a Bayesian framework. We revealed direct and indirect effects of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
(254 reference statements)
2
8
0
Order By: Relevance
“…We estimated that the split between the two major clades of tree ferns occurred around 164 Ma (range 110.8-192.5 Ma), although older (206-176 Ma, Schuettpelz and Pryer, 2009;Testo andSundue, 2016, respectively) andyounger (72-162 Ma, Rothfels et al, 2015;Qi et al, 2018, respectively) ages have been suggested. With a comprehensive sampling of 150 taxa in Cyatheales, Barrera-Redondo et al (2018) estimated the stem age of Cyatheaceae, by far the largest family in the order, to be around 160 Ma, which is similar to both nuclear (157 Ma, Qi et al, 2018) and plastid (174-168 Ma, Schuettpelz and Pryer, 2009;Testo and Sundue, 2016, respectively) studies, but differs considerably from our estimate of 108.6 Ma (range 102.4-170.5 Ma). In our supplemental analysis including the S. lepifera transcriptome and additional fossil calibrations (see Section "Materials and Methods" and Supplementary Figure 6), we recovered a stem age of Cyatheaeceae at 121.1 Ma (range 119.8-124.6 Ma), which is still younger than previous estimates.…”
Section: Cyathealesmentioning
confidence: 99%
“…We estimated that the split between the two major clades of tree ferns occurred around 164 Ma (range 110.8-192.5 Ma), although older (206-176 Ma, Schuettpelz and Pryer, 2009;Testo andSundue, 2016, respectively) andyounger (72-162 Ma, Rothfels et al, 2015;Qi et al, 2018, respectively) ages have been suggested. With a comprehensive sampling of 150 taxa in Cyatheales, Barrera-Redondo et al (2018) estimated the stem age of Cyatheaceae, by far the largest family in the order, to be around 160 Ma, which is similar to both nuclear (157 Ma, Qi et al, 2018) and plastid (174-168 Ma, Schuettpelz and Pryer, 2009;Testo and Sundue, 2016, respectively) studies, but differs considerably from our estimate of 108.6 Ma (range 102.4-170.5 Ma). In our supplemental analysis including the S. lepifera transcriptome and additional fossil calibrations (see Section "Materials and Methods" and Supplementary Figure 6), we recovered a stem age of Cyatheaeceae at 121.1 Ma (range 119.8-124.6 Ma), which is still younger than previous estimates.…”
Section: Cyathealesmentioning
confidence: 99%
“…2005 ; Machado et al. 2016 ; Barrera-Redondo et al. 2018 ), but our study is among the first to show clear evidence for an effect of latitude on rates of mutation accumulation.…”
Section: Discussionmentioning
confidence: 50%
“…I used GenBank's plant database (last updated June 28, 2020) by querying for 'Cyatheales' sequences longer than 400 bp, with a minimum sequence identity of 0.2, and a minimum coverage of 0.65. I complemented the resulting alignments with sequence data retrieved from NCBI's PopSet database (PopSet numbers: 1722035357, 1722034779, 1722034120) and from previously published data 55 ; I incorporated sequences for additional taxa using Clustal2.0 59 and AliView 60 and identified and eliminated species synonyms. The final molecular dataset consisted of DNA sequences for 442 species of Cyatheales (60% of the total diversity) with a total length of 15,249 bp for ten chloroplast regions (protein coding regions: rbcL, atpB, atpA, SQD1, and matK; intergenic spacers: atpB-rbcL, rbcL-accD, trnL-trnF, trnG-trnR, and rps3-rpl16) (Supplementary data 2); the per-site missing information I estimated a maximum likelihood phylogeny with RAxML v.8 61 , using the GTRCAT model, automatic bootstrap replicates (autoMRE), and substitution parameters estimated for each marker independently.…”
Section: Methodsmentioning
confidence: 99%